Depresión en adolescentes de 14 a 16 años y su relación con el consumo de sustancias psicoactivas en la Unidad Educativa Carlos Alberto Aguirre Aviles octubre 2018-abril 2019 - Medina Mancilla, Kerlly Julexsy (2019)
Currently, drug use in adolescence gives rise to mental disorders, which constitute a problem for public health. Mental disorders can have an important effect on the adolescent's development and health. These are associated with several health and social problems, among which we can mention the consumption of tobacco, alcohol, illicit substances or others. Depression can help prevent, improving social performance and the ability to solve problems. The present study is aimed at characterizing depression and the relationship with the consumption of psychoactive substances in adolescents aged 14 to 16 years, in order to reduce the high rate of mental disorder. The viability of this research will help adolescents to understand the relationship between psychoactive substances and depression, as well as the educational unit to implement educational talks for the well-being of adolescents.